Trans-Galen Approach for Embolization of Sphenoparietal Sinus Dural Arteriovenous Fistulas - Dang-Khoi Tran; Minh-Anh Nguyen; Thanh-Tinh Truong; Yuang-Seng Tsuei; Quoc-Tuan Tran (Neurointervention)
A patient in their early 60s presented with a headache and right-sided numbness. Imaging revealed a hemorrhagic lesion in the left thalamus and venous engorgement involving the left sphenoparietal sinus, with drainage through the basal vein of Rosenthal and the superficial middle cerebral vein. The trans-Galen approach was utilized for embolization, successfully obliterating the fistulas using coils without retrograde opacification. Post-procedure angiography demonstrated complete occlusion. This case underscores the trans-Galen approach as a safe and effective strategy for managing complex sphenoparietal sinus dural arteriovenous fistulas, providing direct access while minimizing complications and ensuring procedural success.